DAMPAK USAHA MIKRO KECIL MENENGAH DOMPET MAS DI MASA PANDEMI COVID 19 (Penelitian Kualitatif Deskriptif di Lebak, Banten) - Deden Hidayat (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2022)
Developments in the era of globalization are very dependent on the economic sector as a measure of success carried out by the government. The role of the community in national development, especially in economic development, is Micro, Small and Medium Enterprises (MSMEs). The position of MSMEs in the national economy has an important and strategic role. This condition is very possible because the existence of MSMEs is quite dominant in the Indonesian economy. MSMEs after the economic crisis continued to increase from year to year. This also proves that MSMEs are able to survive in the midst of an economic crisis. MSMEs are also proven to absorb a larger workforce in the national economy. With the number of workers absorbed, the MSME sector is able to increase people's income. Thus, MSMEs are considered to have a strategic role in reducing unemployment and poverty. For the contribution and role of MSMEs, it is important for the government to continue to support MSMEs through strengthening so that their role as pillars in building the nation's economy can run optimally.Keyword : Micro, Small and medium, enterprises Gold Wallet, Covid-19 Pandemic